Implementasi dan Analisis Jaringan WIreless VoIP Dengan Manajemen Routerboard di Politeknik Negeri Malang - Junaedi Adi Prasetyo (Jurnal Jaringan Telekomunikasi, 2015)
In this article, the implementation of wirelessVoIP at State Polytechnic of Malang uses microtic management with the aim of knowing the QoS (Quality of Services) performance between systems without microtic management and systems using microtic management. In the implementation of this system, two tests were carried out, namely QoS testing when without proxy management and when using proxy management. From the two tests, the performance will be compared by doing data compilation using the VQ manager software. The QoS parameters to be taken are delay, jitter, packet loss and throughput. From the measurement it is known that when the VoIP server serves <= 3 calls simultaneously, the MOS value between the managed system (MOS = 3.7) and the system without management (MOS = 3.7) is almost the same because the value of delay and packet loss in the system without management and systems with management did not differ much, namely 107 ms and 83 ms, and the packet loss value was the same, namely 5%. And when serving> 3 simultaneous calls, there is a difference of 0.18 from the MOS value between the managed system (MOS = 3.48) and a system without management (MOS = 3.3) with a value of delay and packet loss for systems without management and systems with management, namely 527 ms and 340 ms, and the packet loss values ??were the same, namely 8% and 7.2%.